Ultra high performance liquid chromatography coupled with triple quadrupole mass spectrometry and chemometric analysis of licorice based on the simultaneous determination of saponins and flavonoids. Issue 15 (19th July 2016) - Jiang, Zhenzuo; Wang, Yuefei; Zheng, Yunfeng; Yang, Jing; Zhang, Lei
Abstract : Licorice is among the most popular herbal medicines and frequently used in traditional medicine, food products, and cosmetics. In China, only Glycyrrhiza uralensis Fisch., Glycyrrhiza inflata Bat. and Glycyrrhiza glabra L. are officially used and are usually processed with honey prior to use. To maintain the quality of commercially available herbal products, a simple, rapid, and reliable ultra high performance liquid chromatography with triple quadrupole mass spectrometry was developed to investigate the major active constituents of commercially available licorice products. Nineteen components were accurately determined, including eight triterpenoid saponins, one triterpene, and ten flavonoids. Subsequently, multivariate statistical analysis methods were employed to further explore and interpret the experimental data. The results indicated that liquiritin apioside may be considered as a candidate index for the quality control of licorice as well as 18β‐glycyrrhizic acid and liquiritin. In addition, both 18β‐glycyrrhizic acid and licorice‐saponin G2 can be used for discrimination between crude and honey‐processed licorice. Furthermore, using 18β‐glycyrrhizic acid and liquiritin as markers, this work revealed that the quality of licorice products may have declined in recent years. This highlights the need for additional effort focused on good agricultural practice during the processing of licorice. In summary, this study provides a valuable reference for the quality assessment of licorice.